Alternatives How We Delayed Economic Growth In Africa - And New Alternatives For The 21st Century - Janvier Kakoko (Toronto [], 2019)
Reviews: "This book is an optimistic material that every young African must Read: the old ways of doing business with Africa are outdated... this book demonstrates a new path for Africa to position itself in the 21st century."- CP 24 ? Toronto"I found your book very interesting. It was a great learning experience for me!" - Lyndsay James" Stumbled on this book, and now I can't put it down."- Anonymous, Internet Follower....this Book, "ALTERNATIVES," is based on a much more different perspective about the way to approach the Africa economy in the 21st Century. In ALTERNATIVES, Mr. Kakoko boldly challenges the current African economic model and presents practical and optimistic economic strategies for African countries to survive the 21st century's Globalized and Complex Economy. His bottom line premises are straightforward: To reach its full potential, Africa needs the right economic model, the right institutions, the right industries, the right investments, the ideal companies - and all of that must come from you, the reader. He also insists on the fact that "Global economy is all about competition - and that won't change in the 21st century..." An economic growth of about four percent made Western Europe the most powerful economic region in the world during the period after the WWII ? a simple focus on Foreign Direct Investments and an industrial-led economy have transformed the Est Asian countries' economy for good - whereas Africa experienced an economic growth of about six to seven percent during the past decade, some African countries experienced a double-digit economic growth, but the continent still the least strong economy in the world ? and that's because there's a missing piece ? that piece is the main focus of this Book. THIS BOOK IS CERTAINLY NOT A STIGMATISATION or fire and fury on those who failed Africa. Instead, it is based on an illustration of new ways never attended in Africa that will allow a more significant number of African populations to recover from unnecessary poverty. Regardless their motivations, today's generation has a role to play in the African development process in the 21st century: On the one hand, if you are young, a businessman or businesswoman, an entrepreneur or an investor interested in engaging with Africa, this book will guide you in how to position yourself and strategically manage your engagements with the whole continent in the 21st century ? and on the other hand, more importantly, if you are aspiring for politics, policymaking, economic activities this book presents a simplified package of economic and political reforms that must be addressed and applied by you, the reader, for Africa to establish a long-term economic development from within the continent in the 21st century. Every generation has its defining works. Now it?s our generation?s turn to do great things. Ideas don?t come out fully formed. They only become clear as you work on them. So, let?s get started.
Keywords: Africa